Afferent Connectivity of the Zebrafish Habenulae - Turner, Katherine J.; Hawkins, Thomas A.; Yáñez, Julián; Anadón, Ramón; Wilson, Stephen W.; Folgueira, Mónica (Frontiers in Neural Circuits, 2016)
The habenulae are bilateral nuclei located in the dorsal diencephalon that are conserved across vertebrates. Here we describe the main afferents to the habenulae in larval and adult zebrafish. We observe afferents from the subpallium, nucleus rostrolateralis, posterior tuberculum, posterior hypothalamic lobe, median raphe, olfactory bulb to the right habenula and from the parapineal to the left  habenula. In addition, we find afferents from a ventrolateral telencephalic nucleus that neurochemical and hodological data identify as the ventral entopeduncular nucleus (vENT), confirming and extending observations of Amo et al. (2014). Fate map and marker studies suggest that vENT originates from the diencephalic prethalamic eminence and extends into the lateral telencephalon from 48 to 120 hpf. No afferents to the habenula were observed from the dorsal entopeduncular nucleus (dENT). Consequently, we confirm that the vENT (and not the dENT) should be considered as the entopeduncular nucleus “proper” in zebrafish. Furthermore, comparison with data in other vertebrates suggests that the vENT is a conserved basal ganglia nucleus, being homologous to the entopeduncular nucleus of mammals (internal segment of the globus pallidus of primates) by both embryonic origin and projections, as previously suggested by Amo et al. (2014). Key words: habenula, connections, afferents, entopeduncular nucleus, posterior tuberculum, basal ganglia, zebrafish